ADSORPTION THERMODYNAMICS OF Cd(II), Ni(II), AND Mg(II) ON 3-MERCAPTO-1,2,4-TRIAZOLE IMMOBILIZED SILICA GEL - Fahmiati Fahmiati; Nuryono Nuryono; Narsito Narsito (Indonesian Journal of Chemistry, 2006)
Thermodynamics study of Cd(II), Ni(II), and Mg(II) adsorption on silica gel immobilized with 3-mercapto-1,2,4-triazole (SG-SH) has been carried out. Three thermodynamic parameters namely adsorption capacity, equilibrium constant and adsorption energy were determined using model of Langmuir adsorption isotherm. Process of adsorption was carried out by mixing metal ion solution in various concentrations (5 - 400 mg/L) with adsorbent in a batch system. The un-adsorbed ions were determined by Atomic Absorption Spectrophotometry (AAS) and the adsorbed ions were differences of ion concentration in solution before and after adsorption process. Parameters of thermodynamics i.e. capacity (a), equilibrium constant (K) and adsorption energy were determined by using the correlation curve of ratio of equilibrium concentration to the amount of adsorbed metal ions versus equilibrium concentration. Results showed that adsorption of metal ions Ni(II), Cd(II) and Mg(II) on adsorbent of silica gel immobilized with mercapto groups tend to follow Type I (monolayer) of Brunauer's classification. Evaluation of thermodynamic adsorption showed that the order of adsorption capacity was Ni(II) < Cd(II) < Mg(II) with relatively low energy adsorption, in a range  of 12 - 18 kJ/mole.